ORNAO ’96 Conference Closing Address Shared Visions & Hallucinations Acquiring a Taste for Chaos - Malone, Beverly (Operating Room Nurses Association of Canada Journal, 1996)
Why would anyone speak about shared visions, or more interestingly, about hallucinations. These are not things that we usually announce to the public. There is some retribution that can occur if you actually announce, “I am presently hallucinating”. I am a Psychiatric Nurse, and I know where they take you when you make those kinds of announcements.